Determination of the Maximum Velocity of Filaments in the in vitro Motility Assay - Bopp, Nasrin; Scheid, Lisa-Mareike; Fink, Rainer H. A.; Rohr, Karl (Frontiers in Physiology, 2019)
The in vitro motility assay (IVMA) is a powerful tool commonly used in basic muscle research and for drug screens with the aim to find treatment options for neuromuscular disorders. In brief, the sliding movement of fluorescence-labeled actin filaments on myosin motor proteins is recorded, and the sliding velocity is analyzed via image analysis methods. Due to low signal-to-noise ratios and large variability in the velocity signal, accurate determination of the maximum sliding velocity is challenging. We introduce a new method and software program named Actin Phase Velocity (ActiPHV). The method extracts the maximum velocity from filament tracking data. Based on simulated and real reference data we show that our method yields a higher accuracy compared to previous methods. As a result, our method enables enhancing the sensitivity of the IVMA to better exploit its full potential.